When the life-cycle ends: the nurse's confrontation with death - Bento, Sandrina (2021)
Background: With the shift of death and dying from home to hospital, in the hospital death process, nurses are inevitably faced with death in their professional context. Accompanying someone at the time of death can be a privilege and an opportunity to give meaning to life, but it is also a time of great exhaustion and emotional overload. It involves having the ability to deal with the suffering of people and one’s own emotions, which is not easy at all and for which the nurse was neither professionally nor naturally prepared. Based on this, the question is how the nurse can develop this emotional competence and mobilize it in the context of care, ensuring quality care and a dignified death for patients at the end of life? Objective: To identify and better understand the strategies developed by nurses to deal with the emotional impact of death and dying. Methods: An integrative literature review with research in the Institutional Repository database of the Portuguese Catholic University and the Portuguese Open Access Scientific Repository. Results: Rationalization, the situation of denial, forging ahead, avoidance, false security, projective identification, patient relationship severance, focus on routines and technique, team sharing, outside-work activities and family support strategies were identified during this study. Conclusions: The intense emotional experience of end-of-life care can generate a disproportionate workload and stress with negative consequences, so it is important that nurses develop strategies that help them deal with these experiences and keep their emotional and spiritual health.